Kajian Glycocalyx bakteri Pada Kontaminasi Ulin (Eusideroxylon zwageri) In-Vitro - Asri Insiana Putri (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2009)
In-Vitro contamination of plant tissue cultures by bacteria is one of the most serious problem in plant micropropagation. Ulin (Eusideroxylon zwageri) bacterial contamination in vitro may survive surface sterization of the explant because they are in interior tissue and some Bacterial spores can also survive the sterilization procedure even if they are un the tissue surface. Bacteria secrete some sort of glycocalyx, an auter viscous covering of fibers extending from the Bacterium. This Study was conducted to examine the colony thickness and to observe the bacteria glycocalyx contaminant of ulin in vitro folowing three surface explant sterization treatments with fungisida, detergent, alkhohol,HgCl2 and Na2CLO3 as antimicrobial agents. The longer the sterilization time the lesser the bacterial colony thickness farmed. Transmission binocular microscopy showed that distribution of glycocalyx material surrounding coccus ulin bacterial contaminant cells were capsulated like Steptococcus lactis or Enterobacter aerogenes.